The amino acid and fiber contents of four different annual forage legumes at full-bloom stage - Ates, Ertan; Coskuntuna, L.; Tekeli, A. S. (Cuban Journal of Agricultural Science, 2010)
The objective of this work was to determine the amino acid and fiber contents of field pea (Pisum arvense L.), Persian clover (Trifolium resupinatum var. typicum Fiori et Paol.), owl-head clover (T. alpestre L.) and mountain clover (T. montanum L.) at full-bloom stage. The investigation was conducted during the 2005-2006 at the Department of Field Crops in the Agricultural Faculty of the Namik Kemal University, Turkey. Owl-head clover and mountain clover were collected from grasslands (43.0 ?N, 26.0 ?E) of the Belovetz village in Razgrad, Bulgaria. Persian clover (line Y) and field pea (line Z) were obtained from the Department of Field Crops, Agriculture Faculty, Namik Kemal University in Tekirdag, Turkey. All samples were analyzed in triplicate. The experimental design was a randomized complete block with three replicates. The amino acid (g kg-1), crude protein (g kg-1), acid detergent fiber (%), and neutral detergent fiber (%) contents were determined. The highest total content (127.1 g kg-1) of amino acid and crude protein (151.3 g kg-1) were found in the field pea in comparison with the means of the other species observed. The amino acids, neutral detergent fiber, and acid detergent fiber were all affected by the different species. The mountain clover had the highest neutral detergent fiber (45.16 %) and acid detergent fiber (34.67 %) values, whereas, the lowest neutral detergent fiber (40.11 %) and acid detergent fiber (30.52 %) were obtained in Persian clover. Field pea, Persian clover, owl-head clover, and mountain clover are more suitable and could be suggested for utilization as fresh or dried feed in livestock. Key words: amino acid, fiber, Pisum arvense L., Trifolium alpestre L., T. resupinatum L., T. montanum L.